Odpowiedź :
Odpowiedź:
[tex]a)\ \ -\frac{1}{4}:(0,5+10,25):0,05-3\frac{1}{2}\cdot(1,2-2\frac{1}{5})+1,5=\\\\=-\frac{1}{4}:10,75:0,05-3,5\cdot(1,2-2,2)+1,5=\\\\=-0,25:0,05:10,75-3,5\cdot(-1)+1,5=-5:10\frac{3}{4}+3,5+1,5=\\\\=-5:\frac{43}{4}+5=-5\cdot\frac{4}{43}+5=-\frac{20}{43}+5=5-\frac{20}{43}=4\frac{43}{43}-\frac{20}{43}=4\frac{23}{43}[/tex]
[tex]b)\ \ -\frac{2}{5}:0,4+84:2,1-5\frac{1}{5}\cdot(2,1-4,4)=-0,4:0,4+40-\frac{26}{5}\cdot(-2,3)=\\\\=-1+40+\frac{\not26^1^3}{5}\cdot\frac{23}{\not10_{5}}=39+\frac{299}{25}=39+11\frac{24}{25}=50\frac{24}{25}[/tex]
[tex]c)\ \ \dfrac{\frac{3}{8}+2\frac{2}{5}}{0,05}-(5^2-3^2)=\dfrac{\frac{15}{40}+2\frac{16}{40}}{\frac{5}{100}}-(25-9)=\dfrac{2\frac{31}{40}}{\frac{1}{20}}-16=2\frac{31}{40}:\frac{1}{20}-16=\\\\\\=\frac{111}{\not40_{2}}\cdot\not20^1-16=\frac{111}{2}-16=55\frac{1}{2}-16=39\frac{1}{2}[/tex]
[tex]d)\ \ 53\frac{2}{7}-\dfrac{1,05}{-4\frac{1}{10}-3,25}=53\frac{2}{7}-\dfrac{\frac{105}{100} }{-4,1-3,25}=53\frac{2}{7}-\dfrac{\frac{21}{20}}{-7,35}=53\frac{2}{7}-\dfrac{\frac{21}{20}}{-\frac{735}{100}}=\\\\\\=53\frac{2}{7}-\frac{21}{20}:(-\frac{735}{100})=53\frac{2}{7}+\frac{21}{20}:\frac{147}{20}=53\frac{2}{7}+\frac{\not21^1}{\not20_{1}}\cdot\frac{\not20^1}{\not147_{7}}=53\frac{2}{7}+\frac{1}{7}=53\frac{3}{7}[/tex]